African Hut model of health: a framework for improving African migrant health in Aotearoa/New Zealand - Badu, Emmanuel; Mpofu, C.; Came, H. (2023)
There is renewed international effort to improve the health and well-being of migrants. For African migrants, theoretical frameworks designed to account for and guide interventions to address the underlying mechanisms that interact to influence health and well-being remain largely underdeveloped. The aim of this study was to address this gap by providing a unique socio-ecological framework with specific entry points for targeted health promotion action aimed at improving the health and well-being of African migrants living in Aotearoa New Zealand. The African Hut model of health was developed through an inductive iterative approach informed by a review of the evidence and semi-structured interviews with key informants. The interviews were conducted in person using one-on-one format and employed to refine initial themes from the literature. A hybrid thematic analysis, involving both inductive and deductive approaches was used to analyse the interview data. The health and well-being of African migrant communities are the outcome of complex interplay of individual, economic, social and structural factors. To protect and promote the health of African communities in Aotearoa requires tailored interventions that centre culture and deliver holistically.